Apical sealing of root canal fillings performed with five different endodontic sealers: analysis by fluid filtration - Bruno Carvalho de Vasconcelos; Ricardo Affonso Bernardes; Marco Antonio Húngaro Duarte; Clóvis Monteiro Bramante; Ivaldo Gomes de Moraes (University of São Paulo, 2011)
OBJECTIVES: To evaluate the sealing ability of five root canal sealers, including two experimental cements (MBP and MTA-Obtura) using the fluid filtration method. MATERIAL AND METHODS: Teeth were divided into 5 study groups: G1-AH Plus; G2-Acroseal; G3Sealapex; G4-MBP; G5-MTA-Obtura; and two controls. Chemical-mechanical preparation was performed with ProFile rotary nickel-titanium instruments 1 mm short of the apical foramen. The sealing ability was evaluated by fluid filtration at 15, 30, and 60 days. RESULTS: The statistical analysis showed significant difference between the materials at different periods (p<0.05). AH Plus and MBP had similar leakage values at 15 and 60 days, alternating with significant reduction at 30 days, while the other materials showed progressive increase in leakage values. Acroseal and Sealapex presented the best results at 15 days and the worst at 60 days. CONCLUSIONS: All sealers evaluated presented fluid leakage, with AH Plus and MBP showing the best results at the end of the experimental period. Acroseal, Sealapex, and MTA-Obtura presented increase in leakage values at longer observation periods.